AKSIOLOGI DAN PRAKTIK: INTERNALISASI NILAI KARAKTER MELALUI PEMBIASAAN BERBAHASA KRAMA ALUS PADA MURID: PEMBIASAAN BAHASA KRAMA ALUS PADA MURID - Sulistyorini Wibowo; Anas Ahmadi (Kawruh: Journal of Language Education, Literature and Local Culture, 2026)
The educational process is not merely the implementation of learning for the transfer of knowledge but also the instilling of character values in students. Likewise, in Javanese language learning, the implementation also includes the instilling of Javanese cultural character values. One of these is in the material on speaking in krama alus language. In krama alus there are values of politeness, humility, respect for others, and also self-respect. The existing problem is that krama alus language is increasingly abandoned by the younger generation, including students in schools. This study discusses the axiological aspects of the philosophy of science in krama alus language, which includes the benefits of applying krama alus language for internalizing values to students in schools, as well as an elaboration of the application of value-based learning theory. The study employed library research. The results indicate that, in general, the younger generation, particularly students, are abandoning the traditional krama alus (higher) language and shifting to Indonesian or ngoko (lower-regular) because they are perceived as easier and more practical. Consequently, the values inherent in this language are slowly disappearing. To address this, efforts are needed to maintain the existence of this language, which indirectly maintains the character values inherent in students. This can be done by familiarizing students with the use of krama alus at school and providing role models for students in this language from teachers.